Nanofiber Carbon-Supported Phthalocyanine Metal Complexes as Solid Electrocatalysts for Lithium-Air Batteries. (10th November 2016) - Arul, Anupriya; Christy, Maria; Oh, Mi Young; Lee, Yun Sung; Nahm, Kee Suk
Abstract: Iron phthalocyanine supported on graphite nanofibers (GNF_FePc) were synthesized using a simple solvothermal process and characterized using various structural analyses. GNF_FePc were employed as bifunctional electrocatalysts in the air cathode of lithium-oxygen batteries. Galvanostatic charge–discharge tests, cyclic voltammetry, and electrochemical impedance spectroscopy were performed to assess the Performance of Li-air batteries. The air-cell delivered a high specific capacity of ∼5500 mAh/g at the first cycle which remained close to 90% of that value after 4 cycles. The reversibility was nearly 100% for all the four cycles with comparatively lower over potential.